Nanogrooves for 2D and 3D Microenvironments of SH-SY5Y Cultures in Brain-on-Chip Technology - Bastiaens, Alex; Sabahi-Kaviani, Rahman; Luttge, Regina (Frontiers in Neuroscience, 2020)
Brain-on-chip (BOC) technology such as nanogrooves and microtunnel structures can advance in vitro neuronal models by providing a platform with better means to maintain, manipulate and analyze neuronal cell cultures. Specifically, nanogrooves have been shown to influence neuronal differentiation, notably the neurite length and neurite direction. Here, we have drawn new results from our experiments using both 2D and 3D neuronal cell culture implementing both flat and nanogrooved substrates. These are used to show a comparison between the number of cells and neurite length as a first indicator for valuable insights into baseline values and expectations that can be generated from these experiments toward design optimization and predictive value of the technology in our BOC toolbox. Also, as a new step toward neuronal cell models with multiple compartmentalized neuronal cell type regions, we fabricated microtunnel devices bonded to both flat and nanogrooved substrates to assess their compatibility with neuronal cell culture. Our results show that with the current experimental protocols using SH-SY5Y cells, we can expect 200 – 400 cells with a total neurite length of approximately 4,000–5,000 μm per 1 mm2 within our BOC devices, with a lower total neurite length for 3D neuronal cell cultures on flat substrates only. There is a statistically significant difference in total neurite length between 2D cell culture on nanogrooved substrates versus 3D cell culture on flat substrates. As extension of our current BOC toolbox for which these indicative parameters would be used, the microtunnel devices show that culture of SH-SY5Y was feasible, though a limited number of neurites extended into microtunnels away from the cell bodies, regardless of using nanogrooved or flat substrates. This shows that the novel combination of microtunnel devices with nanogrooves can be implemented toward neuronal cell cultures, with future improvements to be performed to ensure neurites extend beyond the confines of the wells between the microtunnels. Overall, these results will aid toward creating more robust BOC platforms with improved predictive value. In turn, this can be used to better understand the brain and brain diseases.